PERLINDUNGAN HUKUM TERHADAP PELAPOR YANG MENGETAHUI PERISTIWA TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA MENURUT UNDANG - UNDANG PERLINDUNGAN SAKSI DAN KORBAN - Agung Prabowo, Pidie; Astutik, Sri; Subekti; Marwiyah, Siti (Judge : Jurnal Hukum, 2025)
Abstract This study aims to examine the legal protection provided to whistleblowers who know about narcotics abuse crimes in Indonesia, in accordance with the provisions of the Witness and Victim Protection Law. The method used is a normative juridical approach by analyzing related legal materials, including legislation and legal literature. The results of the study indicate that legal protection for whistleblowers is very important to encourage the public's courage in reporting narcotics crimes. This protection includes confidentiality of the reporter's identity, physical security, and legal protection from retaliation. The obstacles faced are still non-compliance by officials in implementing optimal protection procedures. It is recommended that law enforcement be more serious in providing protection and socializing the rights of whistleblowers so that their data remains safe and secure